Anti-neutrophil cytoplasmic antibodies in new-onset systemic lupus erythematosus - Fang Su; Weiguo Xiao; Pingting Yang; Qingyan Chen; Xiaojie Sun; Tienan Li (Anais Brasileiros de Dermatologia, 2017)
Abstract: Background: The clinical significance of anti-neutrophil cytoplasmic antibodies in patients with new-onset systemic lupus erythematosus, especially in systemic disease accompanied by interstitial lung disease remains to be elucidated. Objectives: This study was designed to investigate the role of anti-neutrophil cytoplasmic antibodies in new-onset systemic lupus erythematosus patients. Methods: A hundred and seven patients with new-onset SLE were enrolled. Presence of anti-neutrophil cytoplasmic antibodies in the sera was assessed by indirect immunofluorescence as well as enzyme linked immunosorbent assay against proteinase-3 and myeloperoxidase. Clinical features and laboratory parameters of patients were also recorded. All patients were subjected to chest X-ray, chest high-resolution computed tomography and pulmonary function test. Results: Forty-five systemic lupus erythematosus patients (45/107, 42%) were seropositive for anti-neutrophil cytoplasmic antibodies. Compared with anti-neutrophil cytoplasmic antibodies-negative patients, the anti-neutrophil cytoplasmic antibodies-positive patients had significantly higher incidence of renal involvement, anemia, and Raynaud's phenomenon as well as decreased serum level of complement 3/complement 4 and elevated erythrocyte sedimentation rate. In addition, there was a positive correlation between serum anti-neutrophil cytoplasmic antibodies level and disease activity of systemic lupus erythematosus. Furthermore, prevalence of interstitial lung disease in the anti-neutrophil cytoplasmic antibodies -positive patients (25/45, 55.6%) was obviously higher than that in the anti-neutrophil cytoplasmic antibodies-negative patients (15/62, 24.2%). Study limitations: The sample size was limited and the criteria for screening new-onset systemic lupus erythematosus patients might produce bias. Conclusions: The level of anti-neutrophil cytoplasmic antibodies in new-onset systemic lupus erythematosus patients correlates positively with the disease activity and the prevalence of interstitial lung disease.